Effect of intrapartum pethidine on the neonatal outcome: is it duration related? - Abdulwahab, Dalia F; Husien, Roziah; Busurerah, Ruqaiah; Awang, Mokhtar; Ismail, Rozihan (2012)
Objectives: To study the effect of pethidine on the intrapartum fetal heart rate (FHR) pattern and to assess the neonatal outcome with regards to the interval between pethidine administration to delivery of the fetus.